TINJAUAN SISTEMATIS HISPATOLOGI GOUT ARTRITIS: PERAN SEL IMUN DALAM PROSES INFLAMASI DAN KERUSAKAN JARINGAN - Larasati, Veny; Parisa, Nita; Valentino, Albert Amadeus; Diba, Msy. Farah (Media Penelitian dan Pengembangan Kesehatan, 2024)
Gout arthritis is a joint inflammation caused by increased uric acid levels, leading to the formation of monosodium urate (MSU) crystals. The study aimed to deepen the understanding of the role of MSU crystals in triggering both acute and chronic inflammatory responses, as well as the formation of tophi, which damage joint and bone tissues. The method used is the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The reviewed articles were obtained from the Science Direct, Semantic Scholar, and PubMed databases using the keywords “Gout Arthritis,” “Histopathology,” “Inflammation,” and “Tophus.” The publication period was limited to 2019-2024. Out of 745 articles found, 12 were selected based on inclusion criteria, which included experimental, observational, and case study reports. The results show that MSU crystals induce inflammation through the infiltration of inflammatory cells such as neutrophils and macrophages. In chronic Gout, the formation of tophi, granulomatous lesions with a crystalline core, leads to bone and joint destruction. Understanding the histopathological aspects is crucial for more accurate diagnosis and more effective management of Gout arthritis. The progression of the disease is related to acute and chronic inflammation, as well as the destructive effects of tophi on joints and bones. In conclusion, MSU crystals play a significant role in triggering inflammation and tissue damage in Gout arthritis, and understanding histopathology can improve diagnostic accuracy and therapeutic efficacy.